ERROR ANALYSIS in the TEACHING of ENGLISH - Hasyim, Sunardi (k@ta: A Biannual Publication on the Study of Language and Literature, 2004)
The main purpose of this article is to discuss the importance of error analysis in the teaching of English as a foreign language. Although errors are bad things in learning English as a foreign language%2C error analysis is advantageous for both learners and teachers. For learners%2C error analysis is needed to show them in what aspect in grammar which is difficult for them%2C where as for teachers%2C it is required to evaluate themselves whether they are successful or not in teaching English.%0D%0AIn this article%2C the writer presented some English sentences containing grammatical errors. These grammatical errors were analyzed based on the theories presented by the linguists. This analysis aimed at showing the students the causes and kinds of the grammatical errors. By this way%2C the students are expected to increase their knowledge on the English grammar. Abstract in Bahasa Indonesia : errors%2C+mistake%2C+over+orrer%2C+covert+error%2C+interference%2C+overgeneralization%2C+grammar%2C+interlingual%2C+intralingual%2C+idiosyncrasies.